Narrative Colors (Comparatismi, 2021)
The specific function of colors as a resource for meaning making in the humans’ life contexts points out their conceptual definition and use within culturally and socially embedded practices. Color is commonly a natural component available throughout all types of culture design and production processes - i.e., a resource for meaning making e communication equal alongside others. The contemporary scientific research analyzing the color effects on behavior confirms the main influence of the colors, each of which triggers very specific emotional states. For example, a storytelling with a dominant red color presence has themes and characters that are powerful, vigorous, defiant, anxious, angry, or romantic. Exploring the origins of the color as an abstract concept and considering it as one of the main links between culture, language and thought, it’s possible to define how, why, and where a color influences the humans existence, the sequential thinking of our memory, that is our life narration.
Keywords: Colors’ language definition; Theory of colors; Basic Color Terms; Light and Dark; Blue; Period Eye; Perceptual Attention